Zero-wastewater-discharge green high-strength inorganic fiber heat insulation plate and preparation method thereof

By using the combination of calcium silica, magnesium fiber or aluminum silicate fiber and silicon dioxide solution and flocculant, to prepare zero -emission wastewater green high -strength inorganic fiber insulation board, solving the waste of resources, pollution emissions and processes in existing technologies Complex issues have achieved the goals of green environmental protection and low -cost production.

CN119349978APending Publication Date: 2025-01-24WUHAN UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411013563.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing inorganic fiber heat insulation plate preparation technology has problems such as waste of resources, pollution emissions, complex processes and high energy consumption, making it difficult to achieve green and environmentally friendly and low-cost production.

Method used

Use calcium silicate and magnesium fiber or aluminum silicate fiber to mix with exfoliating water, and add silica solids and flocculants under the stirring conditions. Realize resource recovery and green cycle.

Benefits of technology

The prepared inorganic fiber thermal insulation board has excellent mechanical performance and thermal insulation performance. The normal temperature thermal conductivity is low, the volume density and the pore rate are high, and the process is simple, low cost and less energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349978A_ABST
    Figure CN119349978A_ABST
Patent Text Reader

Abstract

The invention relates to a zero-wastewater-discharge green high-strength inorganic fiber heat insulation plate and a preparation method thereof. According to the technical scheme, the preparation method comprises the following steps: mixing calcium magnesium silicate fibers or aluminum silicate fibers with deionized water to obtain a mixture I or I '; respectively adding silica sol and a flocculating agent into the mixture I or I 'under a stirring condition, and stirring to obtain two primary mixtures; carrying out suction filtration on the two primary mixtures to obtain two primary filtrates and primary wet blanks, and respectively drying the two wet blanks to prepare two green high-strength inorganic fiber heat insulation plates with zero wastewater discharge; and respectively adding corresponding fibers into the two primary filtrates, stirring, carrying out suction filtration, respectively drying two obtained wet blanks, repeating for 2-3 times, supplementing silica sol and a flocculating agent to the mixture III or II'by mass to obtain two secondary mixtures, and circulating in sequence to prepare two n-time zero-wastewater-discharge green high-strength inorganic fiber heat insulation plates. The material is excellent in mechanical property, low in heat conductivity, small in volume density and high in porosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of inorganic fiber insulation boards, and specifically relates to a zero-wastewater discharge green high-strength inorganic fiber insulation board and a preparation method thereof. Background Art

[0002] With the shortage of energy and the improvement of people's awareness of energy conservation and environmental protection, energy conservation, energy storage and resource reuse have made the requirements for refractory insulation materials in high-temperature fields higher and higher. Inorganic fibers have the characteristics of light weight, low thermal conductivity, small heat capacity, good thermal shock resistance and convenient construction. They have excellent thermal insulation properties and can effectively reduce heat dissipation and heat storage losses. They are widely used in aerospace, military engineering, metallurgy and high-temperature insulation fields. Therefore, people are paying more and more attention to inorganic fiber insulation materials. Among them, inorganic fiber insulation boards are also gradually entering industrial production and daily life. There are many methods for preparing fiber insulation boards, among which wet molding processes are more commonly used, such as vacuum filtration, gel casting, etc. The filtration process can obtain products with high open porosity and good three-dimensional pore connectivity.

[0003] At present, there are technologies for preparing thermal insulation fiber materials, such as document I (Dasiewicz J, Kowaluk G. Characteristics of high-density fibreboard Produced with the use of rice starch as a binder [J]. Annals of Warsaw University of Life Sciences SGGW Forestry and Wood Technology, 2023, 122: 169-181.) The use of rice starch organic matter for modification can only be prepared once and cannot be recycled repeatedly. In addition, the organic matter in the discharged wastewater will decompose and cause pollution, and the resources cannot be recycled.

[0004] Literature II (Ye Yuzuo, Li Hongqiang, Lu Junjie, et al. Preparation and reaction stability of KH-570 modified silica sol [J]. Organic Silicon Materials, 2011, 25 (3): 153-156.) Compared with the unmodified silica sol, the particle size of KH-570 modified silica sol is slightly larger and the particle size distribution is more uniform. However, this modified silica sol cannot be recycled in the process and will discharge wastewater containing toxic substances, causing environmental pollution.

[0005] Document III (Chen Lijun, Jiang Yuanru, Zhang Xuanzhuoyi, Chen Long, et al. Study on methyltriethoxysilane modified silica sol and its hydrophobic properties [J] Coatings Industry, 2012, 42(4)26-28.) uses methyltriethoxysilane to modify industrial-grade silica sol, and uses the immersion pulling method and gravity method to prepare a hydrophobic film on the glass surface to improve the hydrophobicity of the silica sol. The raw materials used in this method are organic compounds, and the process waste contains toxic substances, which will cause pollution when discharged into the environment. The silica sol modified by this method cannot be recycled in the process because it contains organic matter, and is not green and environmentally friendly.

[0006] Document IV (Cheng Z, Li X, Yuan S, et al. Fabrication of ultralight heat-insulating hollow-fiber mullite fiberboards[J]. Ceramics International, 2021, 47(21): 29576-29583.) uses hollow mullite fiber vacuum filtration method to prepare mullite fiberboard. Although this method ensures a low thermal conductivity of 0.0988~0.123W / (m·K), the mullite fiberboard prepared by this method has poor mechanical properties (compressive strength 0.08~0.12MPa). Document V (Pang X, Wang T, Kong J. Fabrication of lightweight ZrO2 fiberboards using hollow ZrO2 fibers. Ceram Int. 2020; 46: 9103-9108.) uses biomorphic ZrO2 hollow fibers and a vacuum filtration molding process to manufacture lightweight ZrO2 fiberboards. Compared with traditional ZrO2 solid fibers, this fiberboard has a lower density and better thermal insulation performance. Although this method ensures a low thermal conductivity (0.101-0.116 W / (m·K) at 500°C), the mechanical properties of the fiberboard are poor (compressive strength is 0.05-0.24 MPa).

[0007] Document VI (Du H, Wang S, Xing Y et al. The dual effect of zirconia fiber on the insulation and mechanical performance of the fumed silica-based thermal insulation material. Ceram Int. 2022; 48: 6657-6662) uses zirconia fiber to improve the strength of fumed silica-based thermal insulation materials and reduce radiation heat transfer, but the density of this fiberboard is relatively high (density is 0.70 g / cm 3 ), the porosity is relatively low (the porosity is 75.0%).

[0008] The patented technology of "A porous thermal insulation fiberboard" (CN202483022U) adopts blow molding, hot grinding and spray gluing methods to produce porous thermal insulation fiberboard, but the process flow is complicated and the production cost and energy consumption are high.

[0009] The patented technology of "A method for preparing a thermal insulation cellulose aerogel composite material" (CN115975251A) solves the poor thermal insulation and flame retardant properties of existing cellulose aerogels. However, the thermal conductivity of the prepared thermal insulation cellulose composite material is as high as 0.0499~0.201W / (m·K) at room temperature, and the process adopts freeze-drying and needs to be sintered at 600℃~1000℃. The process is complex, harsh and energy-intensive.

[0010] The patented technology of "Preparation method of hollow mullite thermal insulation fiber" (CN110156447A) reduces the thermal conductivity of traditional solid mullite fiber by 20%, but the preparation process requires sintering in an oxygen atmosphere, which has high heat consumption cost and great waste of resources.

[0011] The patented technology of "A nano thermal insulation material and its preparation method" (CN113024267A) discloses a mixture of nano alumina, nano silicon dioxide, silicon carbide, glass fiber, ammonium dihydrogen phosphate and aluminum dihydrogen phosphate, ball milling, and drying to obtain nano thermal insulation material powder; the nano thermal insulation material powder is then pressed into shape, dried, and then kept warm at 1000-1200°C for 1-3 hours, and naturally cooled to obtain the nano thermal insulation material. The thermal conductivity of the nano thermal insulation material obtained by this technology is 0.0140-0.0350W / (m·K), but the raw material cost is high and the strength of the obtained nano thermal insulation material is low.

[0012] The patented technology of "a high-strength nano thermal insulation material and its preparation method" (CN201911099302.8) has a large volume density (0.3-1.0 g / cm 3 ) and small apparent porosity. Summary of the invention

[0013] The present invention aims to overcome the defects of the prior art and aims to provide a method for preparing a zero-emission wastewater green high-strength inorganic fiber insulation board with resource recovery, green circulation, no wastewater discharge, simple process, low production cost and low energy consumption; the prepared product not only has excellent mechanical properties, but also has low thermal conductivity, low volume density and high porosity.

[0014] To achieve the above object, the specific steps of the technical solution adopted by the present invention are:

[0015] Step 1: 6.0-8.0 parts by mass of calcium magnesium silicate fiber and 69.0-71.0 parts by mass of deionized water are mixed and stirred rapidly to obtain a first mixture I; or 5.0-6.0 parts by mass of aluminum silicate fiber and 70.0-72.0 parts by mass of deionized water are mixed and stirred rapidly to obtain a first mixture I'.

[0016] Step 2: Under stirring conditions, add 23.0 to 25.0 parts by mass of silica sol to the first mixture I and the first mixture I', respectively, to obtain the first mixture II and the first mixture II'; then take 0.1 to 0.5 parts by mass of a modifier and mix it with 2 to 3 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II and the first mixture II', respectively, and stir to obtain the first mixture III and the first mixture III'.

[0017] Step 3, preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is A1 method or B1 method, the A1 method is carried out according to the following steps 3.1 to 3.2, and the B1 method is carried out according to the following steps 3.1 to 3.3.

[0018] Step 3.1, the first mixed material III and the first mixed material III' are respectively filtered under a vacuum degree of -0.088 to -0.098 MPa to obtain a first filtrate I and a first wet blank I, a first filtrate I' and a first wet blank I'.

[0019] The prepared first wet blank I and first wet blank I' are respectively dried in air atmosphere at 100-110°C for 10-12h and cooled to prepare the first zero-wastewater discharge green high-strength inorganic fiber insulation board I and the first zero-wastewater discharge green high-strength inorganic fiber insulation board I'.

[0020] Step 3.2, add calcium magnesium silicate fiber to the first filtrate I to the mass parts described in step 1, or add aluminum silicate fiber to the first filtrate I' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain the first filtrate II and the first wet blank II, the first filtrate II' and the first wet blank II'.

[0021] The prepared first wet blank II and first wet blank II' are respectively dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the first zero-wastewater discharge green high-strength inorganic fiber insulation board II and the first zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0022] Step 3.3, add calcium magnesium silicate fiber to the first filtrate II to the mass parts described in step 1, or add aluminum silicate fiber to the first filtrate II' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain the first filtrate III and the first wet blank III, the first filtrate III' and the first wet blank III'.

[0023] The first wet blank III and the first wet blank III' are dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the first zero-wastewater discharge green high-strength inorganic fiber insulation board III and the first zero-wastewater discharge green high-strength inorganic fiber insulation board III'.

[0024] Step 3.4, according to method A1 or method B1, add calcium magnesium silicate fiber to the first filtrate II filtered twice or the first filtrate III filtered three times to the mass parts described in step 1, or add aluminum silicate fiber to the first filtrate II' filtered twice or the first filtrate III' filtered three times to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2, respectively, to obtain the second mixture I and the second mixture I'.

[0025] Step 4, according to step 3, prepare the second zero-wastewater discharge green high-strength inorganic fiber insulation board, the preparation method is A2 method or B2 method, the A2 method is carried out according to the following steps 4.1 to 4.2, and the B2 method is carried out according to the following steps 4.1 to 4.3.

[0026] Step 4.1, the second mixture I and the second mixture I' are respectively filtered under a vacuum degree of -0.088 to -0.098 MPa to obtain a second filtrate I and a second wet blank I, a second filtrate I' and a second wet blank I'.

[0027] The prepared second wet blank I and second wet blank I' are respectively dried in an air atmosphere at 100-110° C. for 10-12 hours and cooled to obtain a second zero-wastewater discharge green high-strength inorganic fiber insulation board I and a second zero-wastewater discharge green high-strength inorganic fiber insulation board I'.

[0028] Step 4.2, add calcium magnesium silicate fiber to the second filtrate I to the mass parts described in step 1, or add aluminum silicate fiber to the second filtrate I' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain a second filtrate II and a second wet blank II, a second filtrate II' and a second wet blank II'.

[0029] The prepared second wet blank II and second wet blank II' are respectively dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the second zero-wastewater discharge green high-strength inorganic fiber insulation board II and the second zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0030] Step 4.3, add calcium magnesium silicate fiber to the second filtrate II to the mass parts described in step 1, or add aluminum silicate fiber to the second filtrate II' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain second filtrate III and second wet blank III, second filtrate III' and second wet blank III'.

[0031] The obtained second wet blank III and second wet blank III' are dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the second zero-wastewater discharge green high-strength inorganic fiber insulation board III and the second zero-wastewater discharge green high-strength inorganic fiber insulation board III'.

[0032] Step 4.4, according to method A2 or method B2, add calcium magnesium silicate fiber to the second filtrate II filtered twice or the second filtrate III filtered three times to the mass parts described in step 1, or add aluminum silicate fiber to the second filtrate II' filtered twice or the second filtrate III' filtered three times to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2, respectively, to obtain the third mixture I and the third mixture I'.

[0033] Cycle in sequence.

[0034] Step 2+n, according to step 3, prepare the nth zero-emission wastewater green high-strength inorganic fiber insulation board, the preparation method is An method or Bn method, the An method is carried out according to the following steps 2+n.1~2+n.2, and the Bn method is carried out according to the following steps 2+n.1~2+n.3.

[0035] Step 2+n.1, the nth mixture I and the nth mixture I' are filtered under a vacuum degree of -0.088 to -0.098 MPa to obtain the nth filtrate I and the nth wet blank I, the nth filtrate I' and the nth wet blank I'.

[0036] The prepared nth wet blank I and nth wet blank I' are respectively dried in an air atmosphere at 100-110°C for 10-12h and cooled to obtain the nth zero-wastewater discharge green high-strength inorganic fiber insulation board I and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board I'.

[0037] Step 2+n.2, add calcium magnesium silicate fiber to the nth filtrate I to the mass parts described in step 1, or add aluminum silicate fiber to the nth filtrate I' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain the nth filtrate II and the nth wet blank II, the nth filtrate II' and the nth wet blank II'.

[0038] The prepared nth wet blank II and nth wet blank II' are respectively dried in an air atmosphere at 100-110°C for 10-12 hours and cooled to obtain the nth zero-wastewater discharge green high-strength inorganic fiber insulation board II and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0039] Step 2+n.3, add calcium magnesium silicate fiber to the nth filtrate II to the mass fraction described in step 1, or add aluminum silicate fiber to the nth filtrate II' to the mass fraction described in step 1, and stir and vacuum filter respectively to obtain the nth filtrate III and the nth wet blank III, the nth filtrate III' and the nth wet blank III'.

[0040] The prepared nth wet blank III and nth wet blank III' are respectively dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the nth zero-wastewater discharge green high-strength inorganic fiber insulation board III and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board III'.

[0041] n is a positive integer ≥30.

[0042] The main chemical components of the calcium magnesium silicate fiber are: MgO≥3.7wt%, SiO2≥64.8wt%, CaO≥28.9wt%, Al2O3≤0.8wt%; the diameter of the calcium magnesium silicate fiber is ≤4μm.

[0043] The main chemical components of the aluminum silicate fiber are: Al2O3≥44.0wt%, SiO2≥54.0wt%, Fe2O3≤0.6wt%, Na2O≤0.2wt%, K2O≤0.2wt%; the diameter of the aluminum silicate fiber is ≤4μm.

[0044] The SiO2 content of the silica sol is 20-22 wt %, and the pH value of the silica sol is 9.5-10.5.

[0045] The modifier is one of attapulgite: α-Al2O3: montmorillonite: γ-Al2O3: nano-Al2O3 in a molar ratio of 4:3:1:1:1, 4:2:2:1:1, 4:1:1:2:2, 3:3:2:1:1, 2:3:3:1:1, 1:4:3:1:1, 1:3:3:2:1, and 1:3:2:3:1.

[0046] The α-Al2O3 is milled to a particle size of d using a planetary ball mill at a ball to material ratio of 3:1. 50 The grinding balls of the ball mill are made of corundum, and the ball milling medium is deionized water.

[0047] The rotation speed of the rapid stirring is 1000-1100 r / min.

[0048] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:

[0049] 1. The present invention uses calcium magnesium silicate fiber and deionized water, or aluminum silicate fiber and deionized water to mix respectively, and add silica sol and attapulgite, α-Al2O3, montmorillonite, γ-Al2O3, nano Al2O3 and 2% citric acid aqueous solution as flocculants under stirring conditions to uniformly stir to obtain a mixture. The mixture is filtered and dried to obtain a zero-emission wastewater green high-strength inorganic fiber insulation board. Compared with the existing preparation technology, these raw materials are cheaper and easier to obtain, so the production cost can be reduced, and the preparation process does not require sintering, the process is simple, the operation is convenient, and the cost and energy consumption are low.

[0050] 2. The filtrate generated in the preparation process of the present invention can be repeatedly recycled, no wastewater is discharged, and there is no pollution to the environment; compared with the prior art, such as the organic modification preparation method of starch and coupling agent, the organic modifier used cannot be recycled, and there are toxic substances in the coupling agent, and the discharge of industrial waste liquid into the environment will cause pollution. The filtrate of the present invention can be reused, realizing resource recovery and green circulation process.

[0051] 3. The present invention uses calcium magnesium silicate fiber or aluminum silicate fiber and silica sol as main raw materials, and by adding flocculant, the modifier in the flocculant is more likely to release metal ions (Mg 2+ 、Al 3+ ) combines with silicon ions in the silica sol to form a new metal bond (Si-OM), inhibiting the hydrophilic group -OH on the surface of SiO2 particles in the silica sol from aggregating to the surface with the evaporation of H2O during the drying process, and evenly fixing SiO2 inside the fiberboard by forming a new metal bond. The prepared zero-emission wastewater green high-strength inorganic fiber insulation board has a higher compressive strength, and the internal pores of the modified zero-emission wastewater green high-strength inorganic fiber insulation board are smaller and more uniform, which reduces the thermal conductivity and increases the porosity. Compared with the existing preparation technology, the zero-emission wastewater green high-strength inorganic fiber insulation board prepared by the present invention has better mechanical properties and thermal insulation properties.

[0052] The zero-wastewater-discharge green high-strength inorganic fiber insulation board prepared by the present invention is tested: the volume density is 0.28-0.69 g / cm 3 ; Surface hardness is 26~72HA; Center hardness is: 22~66HA; Compressive strength is 0.22~0.82MPa; Thermal conductivity at room temperature is 0.0677~0.0737W / (m·K).

[0053] Therefore, the present invention has the preparation method of zero-emission wastewater green high-strength inorganic fiber insulation board with resource recovery, green cycle and no wastewater discharge, simple process, low production cost and low energy consumption; the manufactured products not only have excellent mechanical properties and high compressive strength, but also low thermal conductivity, low volume density and high porosity. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 It is the X-ray diffraction pattern of the calcium magnesium silicate fiber used in the present invention;

[0055] Figure 2 It is the X-ray diffraction pattern of the aluminum silicate fiber used in the present invention;

[0056] Figure 3 It is a SEM low and high magnification microstructure picture of a zero-wastewater discharge green high-strength inorganic fiber insulation board prepared by the present invention;

[0057] Figure 4 yes Figure 3 Energy dispersive X-ray spectrogram analysis of the zero-discharge wastewater green high-strength inorganic fiber insulation board shown;

[0058] Figure 5 This is an energy dispersion X-ray spectrum analysis of another zero-wastewater discharge green high-strength inorganic fiber insulation board prepared by the present invention. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods, which does not limit the protection scope of the present invention.

[0060] A zero-wastewater discharge green high-strength inorganic fiber insulation board and a preparation method thereof. The preparation method described in this specific embodiment is:

[0061] Step 1: 6.0-8.0 parts by mass of calcium magnesium silicate fiber and 69.0-71.0 parts by mass of deionized water are mixed and stirred rapidly to obtain a first mixture I; or 5.0-6.0 parts by mass of aluminum silicate fiber and 70.0-72.0 parts by mass of deionized water are mixed and stirred rapidly to obtain a first mixture I'.

[0062] Step 2: Under stirring conditions, add 23.0 to 25.0 parts by mass of silica sol to the first mixture I and the first mixture I', respectively, to obtain the first mixture II and the first mixture II'; then take 0.1 to 0.5 parts by mass of a modifier and mix it with 2 to 3 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II and the first mixture II', respectively, and stir to obtain the first mixture III and the first mixture III'.

[0063] Step 3, preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is A1 method or B1 method, the A1 method is carried out according to the following steps 3.1 to 3.2, and the B1 method is carried out according to the following steps 3.1 to 3.3.

[0064] Step 3.1, the first mixed material III and the first mixed material III' are respectively filtered under a vacuum degree of -0.088 to -0.098 MPa to obtain a first filtrate I and a first wet blank I, a first filtrate I' and a first wet blank I'.

[0065] The prepared first wet blank I and first wet blank I' are respectively dried in air atmosphere at 100-110°C for 10-12h and cooled to prepare the first zero-wastewater discharge green high-strength inorganic fiber insulation board I and the first zero-wastewater discharge green high-strength inorganic fiber insulation board I'.

[0066] Step 3.2, add calcium magnesium silicate fiber to the first filtrate I to the mass parts described in step 1, or add aluminum silicate fiber to the first filtrate I' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain the first filtrate II and the first wet blank II, the first filtrate II' and the first wet blank II'.

[0067] The prepared first wet blank II and first wet blank II' are respectively dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the first zero-wastewater discharge green high-strength inorganic fiber insulation board II and the first zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0068] Step 3.3, add calcium magnesium silicate fiber to the first filtrate II to the mass parts described in step 1, or add aluminum silicate fiber to the first filtrate II' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain the first filtrate III and the first wet blank III, the first filtrate III' and the first wet blank III'.

[0069] The first wet blank III and the first wet blank III' are dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the first zero-wastewater discharge green high-strength inorganic fiber insulation board III and the first zero-wastewater discharge green high-strength inorganic fiber insulation board III'.

[0070] Step 3.4, according to method A1 or method B1, add calcium magnesium silicate fiber to the first filtrate II filtered twice or the first filtrate III filtered three times to the mass parts described in step 1, or add aluminum silicate fiber to the first filtrate II' filtered twice or the first filtrate III' filtered three times to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2, respectively, to obtain the second mixture I and the second mixture I'.

[0071] Step 4, according to step 3, prepare the second zero-wastewater discharge green high-strength inorganic fiber insulation board, the preparation method is A2 method or B2 method, the A2 method is carried out according to the following steps 4.1 to 4.2, and the B2 method is carried out according to the following steps 4.1 to 4.3.

[0072] Step 4.1, the second mixture I and the second mixture I' are respectively filtered under a vacuum degree of -0.088 to -0.098 MPa to obtain a second filtrate I and a second wet blank I, a second filtrate I' and a second wet blank I'.

[0073] The prepared second wet blank I and second wet blank I' are respectively dried in an air atmosphere at 100-110° C. for 10-12 hours and cooled to obtain a second zero-wastewater discharge green high-strength inorganic fiber insulation board I and a second zero-wastewater discharge green high-strength inorganic fiber insulation board I'.

[0074] Step 4.2, add calcium magnesium silicate fiber to the second filtrate I to the mass parts described in step 1, or add aluminum silicate fiber to the second filtrate I' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain a second filtrate II and a second wet blank II, a second filtrate II' and a second wet blank II'.

[0075] The prepared second wet blank II and second wet blank II' are respectively dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the second zero-wastewater discharge green high-strength inorganic fiber insulation board II and the second zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0076] Step 4.3, add calcium magnesium silicate fiber to the second filtrate II to the mass parts described in step 1, or add aluminum silicate fiber to the second filtrate II' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain second filtrate III and second wet blank III, second filtrate III' and second wet blank III'.

[0077] The obtained second wet blank III and second wet blank III' are dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the second zero-wastewater discharge green high-strength inorganic fiber insulation board III and the second zero-wastewater discharge green high-strength inorganic fiber insulation board III'.

[0078] Step 4.4, according to method A2 or method B2, add calcium magnesium silicate fiber to the second filtrate II filtered twice or the second filtrate III filtered three times to the mass parts described in step 1, or add aluminum silicate fiber to the second filtrate II' filtered twice or the second filtrate III' filtered three times to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2, respectively, to obtain the third mixture I and the third mixture I'.

[0079] Cycle in sequence.

[0080] Step 2+n, according to step 3, prepare the nth zero-emission wastewater green high-strength inorganic fiber insulation board, the preparation method is An method or Bn method, the An method is carried out according to the following steps 2+n.1~2+n.2, and the Bn method is carried out according to the following steps 2+n.1~2+n.3.

[0081] Step 2+n.1, the nth mixture I and the nth mixture I' are filtered under a vacuum degree of -0.088 to -0.098 MPa to obtain the nth filtrate I and the nth wet blank I, the nth filtrate I' and the nth wet blank I'.

[0082] The prepared nth wet blank I and nth wet blank I' are respectively dried in an air atmosphere at 100-110°C for 10-12h and cooled to obtain the nth zero-wastewater discharge green high-strength inorganic fiber insulation board I and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board I'.

[0083] Step 2+n.2, add calcium magnesium silicate fiber to the nth filtrate I to the mass parts described in step 1, or add aluminum silicate fiber to the nth filtrate I' to the mass parts described in step 1, and stir and vacuum filter respectively to obtain the nth filtrate II and the nth wet blank II, the nth filtrate II' and the nth wet blank II'.

[0084] The prepared nth wet blank II and nth wet blank II' are respectively dried in an air atmosphere at 100-110°C for 10-12 hours and cooled to obtain the nth zero-wastewater discharge green high-strength inorganic fiber insulation board II and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0085] Step 2+n.3, add calcium magnesium silicate fiber to the nth filtrate II to the mass fraction described in step 1, or add aluminum silicate fiber to the nth filtrate II' to the mass fraction described in step 1, and stir and vacuum filter respectively to obtain the nth filtrate III and the nth wet blank III, the nth filtrate III' and the nth wet blank III'.

[0086] The prepared nth wet blank III and nth wet blank III' are respectively dried in air atmosphere at 100-110°C for 10-12h and cooled to obtain the nth zero-wastewater discharge green high-strength inorganic fiber insulation board III and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board III'.

[0087] n is a positive integer ≥30.

[0088] The main chemical components of the calcium magnesium silicate fiber are: MgO≥3.7wt%; SiO2≥64.8wt%; CaO≥28.9wt%; Al2O3≤0.8wt%.

[0089] The main chemical components of the aluminum silicate fiber are: Al2O3≥44.0wt%; SiO2≥54.0wt%; Fe2O3≤0.6wt%; Na2O≤0.2wt%; K2O≤0.2wt%.

[0090] The SiO2 content of the silica sol is 20-22 wt %, and the pH value of the silica sol is 9.5-10.5.

[0091] The modifier is one of attapulgite: α-Al2O3: montmorillonite: γ-Al2O3: nano-Al2O3 in a molar ratio of 4:3:1:1:1, 4:2:2:1:1, 4:1:1:2:2, 3:3:2:1:1, 2:3:3:1:1, 1:4:3:1:1, 1:3:3:2:1, and 1:3:2:3:1.

[0092] The rotation speed of the rapid stirring is 1000-1100 r / min.

[0093] In this specific implementation mode:

[0094] The diameter of the calcium magnesium silicate fiber is ≤4 μm;

[0095] The diameter of the aluminum silicate fiber is ≤4 μm;

[0096] The α-Al2O3 is milled to a particle size of d using a planetary ball mill at a ball to material ratio of 3:1. 50 The grinding balls of the ball mill are made of corundum, and the ball milling medium is deionized water.

[0097] This will not be described in detail in the embodiments.

[0098] Example 1

[0099] A zero-wastewater-discharge green high-strength inorganic fiber insulation board and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0100] Step 1: Mix 8.0 parts by mass of calcium magnesium silicate fiber and 69.0 parts by mass of deionized water, and stir rapidly to prepare a first mixture I.

[0101] Step 2: Under stirring conditions, add 23.0 parts by mass of silica sol to the first mixture I to obtain the first mixture II; then take 0.1 parts by mass of the modifier and mix it with 2 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II and stir to obtain the first mixture III.

[0102] Step 3: Preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is A1 method, and the A1 method is carried out according to the following steps.

[0103] Step 3.1, filter the first mixed material III under a vacuum condition of -0.088 MPa to obtain a first filtrate I and a first wet blank I.

[0104] The first wet blank I was dried in an air atmosphere at 100° C. for 10 h, and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board I.

[0105] Step 3.2: Add calcium magnesium silicate fiber to the first filtrate I to the mass fraction described in step 1, stir, and vacuum filter to obtain the first filtrate II and the first wet blank II.

[0106] The first wet blank II was dried in an air atmosphere at 100° C. for 10 h, and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board II.

[0107] Step 3.3, add calcium magnesium silicate fiber to the first filtrate II filtered twice to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain the second mixture I.

[0108] Step 4: According to step 3, a second preparation of zero-wastewater discharge green high-strength inorganic fiber insulation board is carried out, and the preparation method is A2, and the A2 method is carried out according to the following steps.

[0109] Step 4.1, filtering the second mixed material I under a vacuum degree of -0.088 MPa to obtain a second filtrate I and a second wet blank I.

[0110] The prepared second wet blank I was dried in an air atmosphere at 100° C. for 10 h, and cooled to obtain a second zero-wastewater-discharge green high-strength inorganic fiber insulation board I.

[0111] Step 4.2: Add calcium magnesium silicate fiber to the second filtrate I to the mass fraction described in step 1, stir, and vacuum filter to obtain a second filtrate II and a second wet blank II.

[0112] The prepared second wet blank II was dried in an air atmosphere at 100° C. for 10 h, and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board II.

[0113] Step 4.3, add calcium magnesium silicate fiber to the second filtrate II filtered twice to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain the third mixture I.

[0114] Cycle in sequence.

[0115] Step 2+n, according to step 3, the preparation of the nth zero-discharge wastewater green high-strength inorganic fiber insulation board is carried out, and the preparation method is An method, and the An method is carried out according to the following steps.

[0116] Step 2+n.1, filter the nth mixed material I under a vacuum degree of -0.088 MPa to obtain the nth filtrate I and the nth wet blank I.

[0117] The prepared nth wet blank I was dried in an air atmosphere at 100° C. for 10 h, and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board I.

[0118] Step 2+n.2, add calcium magnesium silicate fiber to the nth filtrate I to the mass proportion indicated in step 1, stir, and vacuum filter to obtain the nth filtrate II and the nth wet blank II.

[0119] The prepared nth wet blank II was dried in an air atmosphere at 100° C. for 10 h, and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board II.

[0120] Said n is equal to 500.

[0121] The main chemical components of the calcium magnesium silicate fiber are: 3.7wt% MgO; 66.0wt% SiO2; 28.9wt% CaO; and 0.2wt% Al2O3.

[0122] The SiO2 content of the silica sol is 20 wt %, and the pH value of the silica sol is 9.5.

[0123] The modifier is attapulgite: alpha-Al2O3: montmorillonite: gamma-Al2O3: nano-Al2O3, and the molar ratio is 4:3:1:1:1.

[0124] The rotation speed of the rapid stirring is 1000r / min.

[0125] The zero-emission wastewater green high-strength inorganic fiber insulation board prepared in this embodiment was tested: the volume density is 0.30g / cm 3 ; Surface hardness is 28HA; center hardness is 24HA; compressive strength is 0.23MPa; thermal conductivity at room temperature is 0.0679W / (m·K).

[0126] Example 2

[0127] A zero-wastewater-discharge green high-strength inorganic fiber insulation board and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0128] Step 1: Mix 7.0 parts by mass of calcium magnesium silicate fiber and 70 parts by mass of deionized water, and stir rapidly to prepare a first mixture I.

[0129] Step 2: Under stirring conditions, add 24.0 parts by mass of silica sol to the first mixture I to obtain the first mixture II; then take 0.5 parts by mass of the modifier and mix it with 3 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II and stir to obtain the first mixture III.

[0130] Step 3: Preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is B1 method, and the B1 method is carried out according to the following steps.

[0131] Step 3.1, filter the first mixed material III under a vacuum condition of -0.093 MPa to obtain a first filtrate I and a first wet blank I.

[0132] The first wet blank I was dried in an air atmosphere at 105° C. for 11 h, and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board I.

[0133] Step 3.2: Add calcium magnesium silicate fiber to the first filtrate I to the mass fraction described in step 1, stir, and vacuum filter to obtain the first filtrate II and the first wet blank II.

[0134] The first wet blank II was dried in an air atmosphere at 105° C. for 11 h, and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board II.

[0135] Step 3.3, add calcium magnesium silicate fiber to the first filtrate II to the mass fraction described in step 1, stir, and vacuum filter to obtain the first filtrate III and the first wet blank III.

[0136] The first wet blank III obtained was dried in an air atmosphere at 105° C. for 11 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board III.

[0137] Step 3.4, add calcium magnesium silicate fiber to the first filtrate III filtered three times to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain the second mixture I.

[0138] Step 4: According to step 3, a second preparation of zero-wastewater discharge green high-strength inorganic fiber insulation board is carried out, and the preparation method is method B2, and the method B2 is carried out according to the following steps.

[0139] Step 4.1, filtering the second mixed material I under a vacuum degree of -0.093 MPa to obtain a second filtrate I and a second wet blank I.

[0140] The prepared second wet blank I was dried in an air atmosphere at 105° C. for 11 h, and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board I.

[0141] Step 4.2: Add calcium magnesium silicate fiber to the second filtrate I to the mass fraction described in step 1, stir, and vacuum filter to obtain a second filtrate II and a second wet blank II.

[0142] The prepared second wet blank II was dried in an air atmosphere at 105° C. for 11 h, and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board II.

[0143] Step 4.3, adding calcium magnesium silicate fiber to the second filtrate II to the mass fraction described in step 1, stirring, and vacuum filtering to obtain a second filtrate III and a second wet blank III.

[0144] The obtained second wet blank III was dried in an air atmosphere at 105° C. for 11 hours and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board III.

[0145] Step 4.4, add calcium magnesium silicate fiber to the second filtrate III filtered three times to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain the third mixture I.

[0146] Cycle in sequence.

[0147] Step 2+n, according to step 3, the preparation of the nth zero-discharge wastewater green high-strength inorganic fiber insulation board is carried out, and the preparation method is the Bn method, and the Bn method is carried out according to the following steps.

[0148] Step 2+n.1, filter the nth mixed material I under a vacuum degree of -0.093 MPa to obtain the nth filtrate I and the nth wet blank I.

[0149] The prepared nth wet blank I was dried in an air atmosphere at 105° C. for 11 h, and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board I.

[0150] Step 2+n.2, add calcium magnesium silicate fiber to the nth filtrate I to the mass proportion indicated in step 1, stir, and vacuum filter to obtain the nth filtrate II and the nth wet blank II.

[0151] The prepared nth wet blank II was dried in an air atmosphere at 105° C. for 11 h, and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board II.

[0152] Step 2+n.3, add calcium magnesium silicate fiber to the nth filtrate II to the mass fraction described in step 1, stir, and vacuum filter to obtain the nth filtrate III and the nth wet blank III.

[0153] The prepared nth wet blank III was dried in an air atmosphere at 105° C. for 11 h, and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board III.

[0154] Said n is equal to 300.

[0155] The main chemical components of the calcium magnesium silicate fiber are: 4.0wt% MgO; 66.1wt% SiO2; 29.1wt% CaO; and 0.1wt% Al2O3.

[0156] The SiO2 content of the silica sol is 21 wt %, and the pH value of the silica sol is 10.

[0157] The modifier is attapulgite: alpha-Al2O3: montmorillonite: gamma-Al2O3: nano-Al2O3, and the molar ratio is 4:2:2:1:1.

[0158] The rotation speed of the rapid stirring is 1050r / min.

[0159] The zero-emission wastewater green high-strength inorganic fiber insulation board prepared in this embodiment was tested: the volume density was 0.69g / cm 3 ; Surface hardness is 72HA; center hardness is 66HA; compressive strength is 0.82MPa; thermal conductivity at room temperature is 0.0737W / (m·K).

[0160] Example 3

[0161] A zero-wastewater-discharge green high-strength inorganic fiber insulation board and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0162] Step 1: Mix 6.0 parts by mass of calcium magnesium silicate fiber and 71.0 parts by mass of deionized water, and stir rapidly to prepare a first mixture I.

[0163] Step 2: Under stirring conditions, add 25.0 parts by mass of silica sol to the first mixture I to obtain the first mixture II; then take 0.3 parts by mass of the modifier and mix it with 2 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II and stir to obtain the first mixture III.

[0164] Step 3: Preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is A1 method, and the A1 method is carried out according to the following steps.

[0165] Step 3.1, filter the first mixed material IⅡ under a vacuum condition of -0.098 MPa to obtain the first filtrate I and the first wet blank I.

[0166] The first wet blank I was dried in an air atmosphere at 110° C. for 12 h, and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board I.

[0167] Step 3.2: Add calcium magnesium silicate fiber to the first filtrate I to the mass fraction described in step 1, stir, and vacuum filter to obtain the first filtrate II and the first wet blank II.

[0168] The first wet blank II was dried in an air atmosphere at 110° C. for 12 h, and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board II.

[0169] Step 3.3, add calcium magnesium silicate fiber to the first filtrate II filtered twice to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain the second mixture I.

[0170] Step 4: According to step 3, a second preparation of zero-wastewater discharge green high-strength inorganic fiber insulation board is carried out, and the preparation method is A2, and the A2 method is carried out according to the following steps.

[0171] Step 4.1, filtering the second mixed material I under a vacuum degree of -0.098 MPa to obtain a second filtrate I and a second wet blank I.

[0172] The prepared second wet blank I was dried in an air atmosphere at 110° C. for 12 h, and cooled to obtain a second zero-wastewater-discharge green high-strength inorganic fiber insulation board I.

[0173] Step 4.2: Add calcium magnesium silicate fiber to the second filtrate I to the mass fraction described in step 1, stir, and vacuum filter to obtain a second filtrate II and a second wet blank II.

[0174] The prepared second wet blank II was dried in an air atmosphere at 110° C. for 12 h, and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board II.

[0175] Step 4.3, add calcium magnesium silicate fiber to the second filtrate II filtered twice to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain the third mixture I.

[0176] Cycle in sequence.

[0177] Step 2+n, according to step 3, the preparation of the nth zero-discharge wastewater green high-strength inorganic fiber insulation board is carried out, and the preparation method is An method, and the An method is carried out according to the following steps.

[0178] Step 2+n.1, filter the nth mixed material I under a vacuum degree of -0.098 MPa to obtain the nth filtrate I and the nth wet blank I.

[0179] The prepared nth wet blank I was dried in an air atmosphere at 110° C. for 12 h, and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board I.

[0180] Step 2+n.2, add calcium magnesium silicate fiber to the nth filtrate I to the mass proportion indicated in step 1, stir, and vacuum filter to obtain the nth filtrate II and the nth wet blank II.

[0181] The prepared nth wet blank II was dried in an air atmosphere at 110° C. for 12 h, and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board II.

[0182] Said n is equal to 100.

[0183] The main chemical components of the calcium magnesium silicate fiber are: 5wt% MgO; 64.8wt% SiO2; 29.2wt% CaO; and 0.4wt% Al2O3.

[0184] The SiO2 content of the silica sol is 22 wt %, and the pH value of the silica sol is 10.5.

[0185] The modifier is attapulgite: alpha-Al2O3: montmorillonite: gamma-Al2O3: nano-Al2O3, and the molar ratio is 4:1:1:2:2.

[0186] The rotation speed of the rapid stirring is 1100r / min.

[0187] The zero-emission wastewater green high-strength inorganic fiber insulation board prepared in this embodiment was tested: the volume density was 0.52g / cm 3 ; Surface hardness is 49HA; center hardness is 40HA; compressive strength is 0.65MPa; thermal conductivity at room temperature is 0.0712W / (m·K).

[0188] Example 4

[0189] A zero-wastewater-discharge green high-strength inorganic fiber insulation board and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0190] Step 1: 5.0 parts by mass of aluminum silicate fiber and 70.0 parts by mass of deionized water are mixed and stirred rapidly to obtain a first mixture I'.

[0191] Step 2: Under stirring conditions, add 25.0 parts by mass of silica sol to the first mixture I' to obtain the first mixture II'; then take 0.2 parts by mass of the modifier and mix it with 2 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II' and stir to obtain the first mixture III'.

[0192] Step 3: Preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is A1 method, and the A1 method is carried out according to the following steps.

[0193] Step 3.1, filtering the first mixed material III' under a vacuum degree of -0.088 MPa to obtain a first filtrate I' and a first wet blank I'.

[0194] The first wet blank I' was dried in an air atmosphere at 100° C. for 10 h, and then cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board I'.

[0195] Step 3.2: Add aluminum silicate fiber to the first filtrate I' to the mass fraction as described in step 1, stir, and vacuum filter to obtain the first filtrate II' and the first wet blank II'.

[0196] The first wet blank II' was dried in an air atmosphere at 100°C for 10 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board II'.

[0197] Step 3.3, add aluminum silicate fiber to the first filtrate II' obtained by suction filtration twice to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain the second mixture I'.

[0198] Step 4: According to step 3, a second preparation of zero-wastewater discharge green high-strength inorganic fiber insulation board is carried out, and the preparation method is A2 method, and the A2 method is carried out according to the following steps.

[0199] Step 4.1, filtering the second mixed material I' under a vacuum degree of -0.088 MPa to obtain a second filtrate I' and a second wet blank I'.

[0200] The obtained second wet blank I' was dried in an air atmosphere at 100° C. for 10 h, and cooled to obtain a second zero-wastewater discharge green high-strength inorganic fiber insulation board I'.

[0201] Step 4.2, adding aluminum silicate fiber to the second filtrate I' to the mass fraction in step 1, stirring, vacuum filtering, second filtrate II' and second wet blank II'.

[0202] The prepared second wet blank II' was dried in an air atmosphere at 100°C for 10 hours and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board II'.

[0203] Step 4.3, adding aluminum silicate fiber to the second filtrate II' obtained by suction filtration twice to the mass parts described in step 1, and then adding silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain a third mixture I'.

[0204] Cycle in sequence.

[0205] Step 2+n, according to step 3, the preparation of the nth zero-discharge wastewater green high-strength inorganic fiber insulation board is carried out, and the preparation method is An method, and the An method is carried out according to the following steps.

[0206] Step 2+n.1, filtering the nth mixed material I' under a vacuum degree of -0.088 MPa to obtain the nth filtrate I' and the nth wet blank I'.

[0207] The prepared nth wet blank I' was dried in an air atmosphere at 100°C for 10 hours and cooled to obtain the nth zero-wastewater discharge green high-strength inorganic fiber insulation board I'.

[0208] Step 2+n.2, add aluminum silicate fiber to the nth filtrate I' to the mass fraction described in step 1, stir, and vacuum filter to obtain the nth filtrate II' and the nth wet blank II'.

[0209] The prepared nth wet blank II' was dried in an air atmosphere at 100°C for 10 hours and cooled to obtain the nth zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0210] Said n is equal to 500.

[0211] The main chemical components of the aluminum silicate fiber are: Al2O3 is 44.0wt%; SiO2 is 54.0wt%; Fe2O3 is 0.6wt%; Na2O is 0.2wt%; and K2O is 0.2wt%.

[0212] The SiO2 content of the silica sol is 20 wt %, and the pH value of the silica sol is 9.5.

[0213] The modifier is attapulgite: alpha-Al2O3: montmorillonite: gamma-Al2O3: nano-Al2O3, and the molar ratio is 3:3:2:1:1.

[0214] The rotation speed of the rapid stirring is 1000r / min.

[0215] The zero-emission wastewater green high-strength inorganic fiber insulation board prepared in this embodiment was tested: the volume density was 0.28g / cm 3 ; Surface hardness is 26HA; center hardness is 22HA; compressive strength is 0.22MPa; thermal conductivity at room temperature is 0.0677W / (m·K).

[0216] Example 5

[0217] A zero-wastewater-discharge green high-strength inorganic fiber insulation board and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0218] Step 1: 6.0 parts by mass of aluminum silicate fiber and 70.5 parts by mass of deionized water are mixed and stirred rapidly to obtain a first mixture I'.

[0219] Step 2: Under stirring conditions, add 24.0 parts by mass of silica sol to the first mixture I' to obtain the first mixture II'; then take 0.5 parts by mass of the modifier and mix it with 3 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II' and stir to obtain the first mixture III'.

[0220] Step 3: Preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is B1 method, and the B1 method is carried out according to the following steps.

[0221] Step 3.1, filtering the first mixed material III' under a vacuum degree of -0.093 MPa to obtain a first filtrate I' and a first wet blank I'.

[0222] The first wet blank I' was dried in an air atmosphere at 105° C. for 11 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board I'.

[0223] Step 3.2: Add aluminum silicate fiber to the first filtrate I' to the mass fraction as described in step 1, stir, and vacuum filter to obtain the first filtrate II' and the first wet blank II'.

[0224] The first wet blank II' was dried in an air atmosphere at 105°C for 11 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board II'.

[0225] Step 3.3, adding aluminum silicate fiber to the first filtrate II' to the mass fraction as described in step 1, stirring, and vacuum filtering to obtain the first filtrate III' and the first wet blank III'.

[0226] The first wet blank III' was dried in an air atmosphere at 105°C for 11 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board III'.

[0227] Step 3.4, add aluminum silicate fiber to the first filtrate III' obtained by suction filtration three times to the mass parts of step 1, and then add silica sol, flocculant and deionized water to the mass parts of step 2 to obtain the second mixture I'.

[0228] Step 4: According to step 3, a second preparation of zero-wastewater discharge green high-strength inorganic fiber insulation board is carried out. The preparation method is method B2, and the method B2 is carried out according to the following steps.

[0229] Step 4.1, filtering the second mixed material I' under a vacuum degree of -0.093 MPa to obtain a second filtrate I' and a second wet blank I'.

[0230] The obtained second wet blank I' was dried in an air atmosphere at 105°C for 11 hours and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board I'.

[0231] Step 4.2, adding aluminum silicate fiber to the second filtrate I' to the mass fraction in step 1, stirring, vacuum filtering, second filtrate II' and second wet blank II'.

[0232] The prepared second wet blank II' was dried in an air atmosphere at 105°C for 11 hours, and cooled to obtain a second zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0233] Step 4.3, adding aluminum silicate fiber to the second filtrate II' to the mass fraction in step 1, stirring, and vacuum filtering to obtain a third filtrate III' and a third wet blank III'.

[0234] The third wet blank III and the third wet blank III' were dried in an air atmosphere at 105° C. for 11 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board III'.

[0235] Step 4.4, add aluminum silicate fiber to the second filtrate II' obtained by suction filtration three times to the mass parts of step 1, and then add silica sol, flocculant and deionized water to the mass parts of step 2 to obtain the third mixture I'.

[0236] Cycle in sequence.

[0237] Step 2+n, according to step 3, the preparation of the nth zero-discharge wastewater green high-strength inorganic fiber insulation board is carried out, and the preparation method is the Bn method, and the Bn method is carried out according to the following steps.

[0238] Step 2+n.1, filtering the nth mixed material I' under a vacuum degree of -0.093 MPa to obtain the nth filtrate I' and the nth wet blank I'.

[0239] The prepared nth wet blank I' was dried in an air atmosphere at 105°C for 11 hours, and cooled to obtain the nth zero-emission wastewater green high-strength inorganic fiber insulation board I'.

[0240] Step 2+n.2, add aluminum silicate fiber to the nth filtrate I' to the mass fraction described in step 1, stir, and vacuum filter to obtain the nth filtrate II' and the nth wet blank II'.

[0241] The prepared nth wet blank II' was dried in an air atmosphere at 105°C for 11 hours and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board II'.

[0242] Step 2+n.3, add aluminum silicate fiber to the nth filtrate II' to the mass fraction as described in step 1, stir, and vacuum filter to obtain the nth filtrate III' and the nth wet blank III'.

[0243] The prepared nth wet blank III' was dried in an air atmosphere at 105°C for 11 hours, and cooled to obtain the nth zero-wastewater discharge green high-strength inorganic fiber insulation board III'.

[0244] Said n is equal to 400.

[0245] The main chemical components of the aluminum silicate fiber are: Al2O3 is 44.5wt%; SiO2 is 54.5wt%; Fe2O3 is 0.4wt%; Na2O is 0.18wt%; and K2O is 0.13wt%.

[0246] The SiO2 content of the silica sol is 21 wt %, and the pH value of the silica sol is 10.0.

[0247] The modifier is attapulgite: alpha-Al2O3: montmorillonite: gamma-Al2O3: nano-Al2O3, and the molar ratio is 2:3:3:1:1.

[0248] The rotation speed of the rapid stirring is 1050r / min.

[0249] The zero-emission wastewater green high-strength inorganic fiber insulation board prepared in this embodiment was tested: the volume density was 0.67g / cm 3 ; Surface hardness is 70HA; center hardness is 65HA; compressive strength is 0.79MPa; thermal conductivity at room temperature is 0.0732W / (m·K).

[0250] Example 6

[0251] A zero-wastewater-discharge green high-strength inorganic fiber insulation board and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0252] Step 1: 5.0 parts by mass of aluminum silicate fiber and 71.5 parts by mass of deionized water are mixed and stirred rapidly to obtain a first mixture I'.

[0253] Step 2: Under stirring conditions, add 23.5 parts by mass of silica sol to the first mixture I' to obtain the first mixture II'; then take 0.4 parts by mass of the modifier and mix it with 2 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II' and stir to obtain the first mixture III'.

[0254] Step 3: Preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is A1 method, and the A1 method is carried out according to the following steps.

[0255] Step 3.1, filtering the first mixed material III' under a vacuum degree of -0.098 MPa to obtain a first filtrate I' and a first wet blank I'.

[0256] The first wet blank I' was dried in an air atmosphere at 110° C. for 12 h, and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board I'.

[0257] Step 3.2: Add aluminum silicate fiber to the first filtrate I' to the mass fraction as described in step 1, stir, and vacuum filter to obtain the first filtrate II' and the first wet blank II'.

[0258] The first wet blank II' was dried in an air atmosphere at 110°C for 12 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board II'.

[0259] Step 3.3, add aluminum silicate fiber to the first filtrate II' obtained by suction filtration twice to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain the second mixture I'.

[0260] Step 4: According to step 3, a second preparation of zero-wastewater discharge green high-strength inorganic fiber insulation board is carried out, and the preparation method is A2 method, and the A2 method is carried out according to the following steps.

[0261] Step 4.1, filtering the second mixed material I' under a vacuum degree of -0.098 MPa to obtain a second filtrate I' and a second wet blank I'.

[0262] The obtained second wet blank I' was dried in an air atmosphere at 110° C. for 12 h, and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board I'.

[0263] Step 4.2, adding aluminum silicate fiber to the second filtrate I' to the mass fraction in step 1, stirring, vacuum filtering, second filtrate II' and second wet blank II'.

[0264] The obtained second wet blank II' was dried in an air atmosphere at 110°C for 12 hours and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board II'.

[0265] Step 4.3, adding aluminum silicate fiber to the second filtrate II' obtained by suction filtration twice to the mass parts described in step 1, and then adding silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain a third mixture I'.

[0266] Cycle in sequence.

[0267] Step 2+n, according to step 3, the preparation of the nth zero-discharge wastewater green high-strength inorganic fiber insulation board is carried out, and the preparation method is An method, and the An method is carried out according to the following steps.

[0268] Step 2+n.1, filtering the nth mixed material I' under a vacuum degree of -0.098 MPa to obtain the nth filtrate I' and the nth wet blank I'.

[0269] The prepared nth wet blank I' was dried in an air atmosphere at 110° C. for 12 h, and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board I'.

[0270] Step 2+n.2, add aluminum silicate fiber to the nth filtrate I' to the mass fraction described in step 1, stir, and vacuum filter to obtain the nth filtrate II' and the nth wet blank II'.

[0271] The prepared nth wet blank II' was dried in an air atmosphere at 110°C for 12 hours and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board II'.

[0272] Said n is equal to 200.

[0273] The main chemical components of the aluminum silicate fiber are: Al2O3 is 45.0wt%; SiO2 is 54.3wt%; Fe2O3 is 0.1wt%; Na2O is 0.15wt%; and K2O is 0.11wt%.

[0274] The SiO2 content of the silica sol is 22 wt %, and the pH value of the silica sol is 10.5.

[0275] The modifier is attapulgite: alpha-Al2O3: montmorillonite: gamma-Al2O3: nano-Al2O3, and the molar ratio is 1:4:3:1:1.

[0276] The rotation speed of the rapid stirring is 1100r / min.

[0277] The zero-emission wastewater green high-strength inorganic fiber insulation board prepared in this embodiment was tested: the volume density was 0.59g / cm 3 ; Surface hardness is 60HA; center hardness is 55HA; compressive strength is 0.65MPa; thermal conductivity at room temperature is 0.0711W / (m·K).

[0278] Example 7

[0279] A zero-wastewater-discharge green high-strength inorganic fiber insulation board and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0280] Step 1: 6.0 parts by mass of aluminum silicate fiber and 71.0 parts by mass of deionized water are mixed and stirred rapidly to obtain a first mixture I'.

[0281] Step 2: Under stirring conditions, add 23.0 parts by mass of silica sol to the first mixture I' to obtain the first mixture II'; then take 0.3 parts by mass of the modifier and mix it with 2.5 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II' and stir to obtain the first mixture III'.

[0282] Step 3: Preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is B1 method, and the B1 method is carried out according to the following steps.

[0283] Step 3.1, filtering the first mixed material III' under a vacuum degree of -0.090 MPa to obtain a first filtrate I' and a first wet blank I'.

[0284] The first wet blank I' was dried in an air atmosphere at 110° C. for 10.5 h, and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board I'.

[0285] Step 3.2: Add aluminum silicate fiber to the first filtrate I' to the mass fraction as described in step 1, stir, and vacuum filter to obtain the first filtrate II' and the first wet blank II'.

[0286] The first wet blank II' was dried in an air atmosphere at 110°C for 10.5 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board II'.

[0287] Step 3.3, adding aluminum silicate fiber to the first filtrate II' to the mass fraction as described in step 1, stirring, and vacuum filtering to obtain the first filtrate III' and the first wet blank III'.

[0288] The first wet blank III' was dried in an air atmosphere at 110°C for 10.5 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board III'.

[0289] Step 3.4, add aluminum silicate fiber to the first filtrate III' obtained by suction filtration three times to the mass parts of step 1, and then add silica sol, flocculant and deionized water to the mass parts of step 2 to obtain the second mixture I'.

[0290] Step 4: According to step 3, a second preparation of zero-wastewater discharge green high-strength inorganic fiber insulation board is carried out, and the preparation method is method B2, and the method B2 is carried out according to the following steps.

[0291] Step 4.1, filtering the second mixed material I' under a vacuum degree of -0.090 MPa to obtain a second filtrate I' and a second wet blank I'.

[0292] The obtained second wet blank I' was dried in an air atmosphere at 110°C for 10.5 hours and cooled to obtain a second zero-wastewater emission green high-strength inorganic fiber insulation board I'.

[0293] Step 4.2, adding aluminum silicate fiber to the second filtrate I' to the mass fraction in step 1, stirring, vacuum filtering, second filtrate II' and second wet blank II'.

[0294] The prepared second wet blank II' was dried in an air atmosphere at 110°C for 10.5 hours and cooled to obtain a second zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0295] Step 4.3, adding aluminum silicate fiber to the second filtrate II' to the mass fraction in step 1, stirring, and vacuum filtering to obtain a third filtrate III' and a third wet blank III'.

[0296] The third wet blank III and the third wet blank III' were dried in an air atmosphere at 110° C. for 10.5 h and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board III'.

[0297] Step 4.4, add aluminum silicate fiber to the second filtrate II' obtained by suction filtration three times to the mass parts of step 1, and then add silica sol, flocculant and deionized water to the mass parts of step 2 to obtain the third mixture I'.

[0298] Cycle in sequence.

[0299] Step 2+n, according to step 3, the preparation of the nth zero-discharge wastewater green high-strength inorganic fiber insulation board is carried out, and the preparation method is the Bn method, and the Bn method is carried out according to the following steps.

[0300] Step 2+n.1, filtering the nth mixed material I' under a vacuum degree of -0.090 MPa to obtain the nth filtrate I' and the nth wet blank I'.

[0301] The prepared nth wet blank I' was dried in an air atmosphere at 110°C for 10.5 hours and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board I'.

[0302] Step 2+n.2, add aluminum silicate fiber to the nth filtrate I' to the mass fraction described in step 1, stir, and vacuum filter to obtain the nth filtrate II' and the nth wet blank II'.

[0303] The prepared nth wet blank II' was dried in an air atmosphere at 110°C for 10.5 hours and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board II'.

[0304] Step 2+n.3, add aluminum silicate fiber to the nth filtrate II' to the mass fraction as described in step 1, stir, and vacuum filter to obtain the nth filtrate III' and the nth wet blank III'.

[0305] The prepared nth wet blank III' was dried in an air atmosphere at 110°C for 10.5 hours and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board III'.

[0306] Said n is equal to 80.

[0307] The main chemical components of the aluminum silicate fiber are: Al2O3 is 44.6wt%; SiO2 is 54.1wt%; Fe2O3 is 0.2wt%; Na2O is 0.17wt%; and K2O is 0.16wt%.

[0308] The SiO2 content of the silica sol is 20.5 wt %, and the pH value of the silica sol is 9.8.

[0309] The modifier is attapulgite: alpha-Al2O3: montmorillonite: gamma-Al2O3: nano-Al2O3, and the molar ratio is 1:3:3:2:1.

[0310] The rotation speed of the rapid stirring is 1030r / min.

[0311] The zero-emission wastewater green high-strength inorganic fiber insulation board prepared in this embodiment was tested: the volume density was 0.48g / cm 3 ; Surface hardness is 49HA; center hardness is 44HA; compressive strength is 0.52MPa; thermal conductivity at room temperature is 0.0692W / (m·K).

[0312] Example 8

[0313] A zero-wastewater-discharge green high-strength inorganic fiber insulation board and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0314] Step 1: 5.5 parts by mass of aluminum silicate fiber and 72 parts by mass of deionized water are mixed and stirred rapidly to obtain a first mixture I'.

[0315] Step 2: Under stirring conditions, add 24.5 parts by mass of silica sol to the first mixture I' to obtain the first mixture II'; then take 0.1 parts by mass of the modifier and mix it with 3 parts by mass of a 2wt% citric acid aqueous solution to obtain a flocculant; then add the flocculant to the first mixture II' and stir to obtain the first mixture III'.

[0316] Step 3: Preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is A1 method, and the A1 method is carried out according to the following steps.

[0317] Step 3.1, filtering the first mixed material III' under a vacuum degree of -0.095 MPa to obtain a first filtrate I' and a first wet blank I'.

[0318] The first wet blank I' was dried in an air atmosphere at 110° C. for 11.5 h, and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board I'.

[0319] Step 3.2: Add aluminum silicate fiber to the first filtrate I' to the mass fraction as described in step 1, stir, and vacuum filter to obtain the first filtrate II' and the first wet blank II'.

[0320] The first wet blank II' was dried in an air atmosphere at 110°C for 11.5 hours and cooled to obtain the first zero-wastewater-discharge green high-strength inorganic fiber insulation board II'.

[0321] Step 3.3, add aluminum silicate fiber to the first filtrate II' obtained by suction filtration twice to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain the second mixture I'.

[0322] Step 4: According to step 3, a second preparation of zero-wastewater discharge green high-strength inorganic fiber insulation board is carried out, and the preparation method is A2 method, and the A2 method is carried out according to the following steps.

[0323] Step 4.1, filtering the second mixed material I' under a vacuum degree of -0.095 MPa to obtain a second filtrate I' and a second wet blank I'.

[0324] The obtained second wet blank I' was dried in an air atmosphere at 110° C. for 11.5 h, and cooled to obtain a second zero-wastewater-discharge green high-strength inorganic fiber insulation board I'.

[0325] Step 4.2, adding aluminum silicate fiber to the second filtrate I' to the mass fraction in step 1, stirring, vacuum filtering, second filtrate II' and second wet blank II'.

[0326] The prepared second wet blank II' was dried in an air atmosphere at 110°C for 11.5 hours, and cooled to obtain a second zero-wastewater discharge green high-strength inorganic fiber insulation board II'.

[0327] Step 4.3, adding aluminum silicate fiber to the second filtrate II' obtained by suction filtration twice to the mass parts described in step 1, and then adding silica sol, flocculant and deionized water to the mass parts described in step 2 to obtain a third mixture I'.

[0328] Cycle in sequence.

[0329] Step 2+n, according to step 3, the preparation of the nth zero-discharge wastewater green high-strength inorganic fiber insulation board is carried out, and the preparation method is An method, and the An method is carried out according to the following steps.

[0330] Step 2+n.1, filtering the nth mixed material I' under a vacuum degree of -0.095 MPa to obtain the nth filtrate I' and the nth wet blank I'.

[0331] The prepared nth wet blank I' was dried in an air atmosphere at 110°C for 11.5 hours and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board I'.

[0332] Step 2+n.2, add aluminum silicate fiber to the nth filtrate I' to the mass fraction described in step 1, stir, and vacuum filter to obtain the nth filtrate II' and the nth wet blank II'.

[0333] The prepared nth wet blank II' was dried in an air atmosphere at 110°C for 11.5 hours and cooled to obtain the nth zero-wastewater-discharge green high-strength inorganic fiber insulation board II'.

[0334] Said n is equal to 30.

[0335] The main chemical components of the aluminum silicate fiber are: Al2O3 is 44.3wt%; SiO2 is 54.7wt%; Fe2O3 is 0.5wt%; Na2O is 0.1wt%; and K2O is 0.14wt%.

[0336] The SiO2 content of the silica sol is 21.5 wt %, and the pH value of the silica sol is 10.2.

[0337] The modifier is attapulgite: alpha-Al2O3: montmorillonite: gamma-Al2O3: nano-Al2O3, and the molar ratio is 1:3:2:3:1.

[0338] The rotation speed of the rapid stirring is 1080r / min.

[0339] The zero-emission wastewater green high-strength inorganic fiber insulation board prepared in this embodiment was tested: the volume density was 0.32g / cm 3 ; Surface hardness is 35HA; center hardness is 31HA; compressive strength is 0.39MPa; thermal conductivity at room temperature is 0.0685W / (m·K).

[0340] Compared with the prior art, this specific implementation has the following positive effects:

[0341] 1. This specific embodiment uses calcium magnesium silicate fiber or aluminum silicate fiber such as Figure 1 or Figure 2 As shown, Figure 1 is the X-ray diffraction pattern of the calcium magnesium silicate fiber used in Example 1, Figure 2 is the X-ray diffraction pattern of the aluminum silicate fiber used in Example 4. Figure 1 It can be seen that the calcium magnesium silicate fiber exhibits an amorphous phase; Figure 2It can be seen that the aluminum silicate fiber exhibits an amorphous phase. In this specific embodiment, calcium magnesium silicate fiber or aluminum silicate fiber is mixed with deionized water, and then silica sol and flocculant are added respectively under stirring conditions, and stirred to obtain two primary mixtures; the two primary mixtures are filtered to obtain two primary filtrates and a primary wet blank, and the two wet blanks are dried separately to obtain two primary zero-discharge wastewater green high-strength inorganic fiber insulation boards; the corresponding fibers are added to the two primary filtrates, stirred, and filtered, and the two wet blanks are dried separately, and repeated 2 to 3 times, and silica sol and flocculant are added to the mass parts of the mixture III or III' to obtain two secondary mixtures, which are circulated in sequence to obtain two n-time zero-discharge wastewater green high-strength inorganic fiber insulation boards. Compared with the existing preparation technology, the cost of this specific embodiment is lower and easier to obtain, so the production cost can be reduced, and the preparation process does not require sintering, the process is simple, the operation is convenient, and the cost and energy consumption are low.

[0342] 2. The filtrate generated in the preparation process of this specific embodiment can be repeatedly recycled, no wastewater is discharged, and there is no pollution to the environment; compared with the existing technology, such as the organic modification preparation method of starch and coupling agent, the organic modifier used cannot be recycled, and there are toxic substances in the coupling agent, and the discharge of industrial waste liquid into the environment will cause pollution. The filtrate of this specific embodiment can be reused, realizing resource recovery and green circulation process.

[0343] 3. This specific embodiment uses calcium magnesium silicate fiber or aluminum silicate fiber and silica sol as the main raw materials to prepare a zero-discharge wastewater green high-strength inorganic fiber insulation board such as Figure 3 to Figure 5 As shown: Figure 3 are SEM low and high magnification microstructure images of the thermal insulation fiberboard prepared in Example 1; Figure 4 is an energy dispersive X-ray spectrogram analysis of the thermal insulation fiberboard prepared in Example 1; Figure 5 This is an energy dispersive X-ray spectroscopy analysis of the thermal insulation fiberboard prepared in Example 2. Figure 3 From a, b, c (different magnifications), we can see that: Figure 3 a. Figure 3 b Low-power (300, 500) magnifying glass shows a highly porous network skeleton with smooth fiber surfaces, intertwined to form a three-dimensional structure. Figure 3 c Under a high-power (1000) magnifying glass, it can be seen that the silica sol is attached to the three-dimensional structure formed by the fibers. The fibers are loosely arranged, the gaps between the fibers are large, and the porosity is high. Figure 4 middle, Figure 4 a1 is the internal cross-sectional distribution of the fiberboard, Figure 4 a2 is the Si element distribution diagram of the internal cross section of the fiberboard; Figure 4It can be seen that the Si element is distributed between the fiberboards, but is concentrated in large quantities on the surface of the fiberboard. Figure 5 middle, Figure 5 b1 is the internal cross-sectional distribution of the fiberboard, Figure 5 b2 is the Si element distribution diagram of the internal cross section of the fiberboard. Figure 5 It can be clearly seen that the Si element is evenly distributed between the fiberboards and does not aggregate on the surface, indicating that the silica sol is more evenly fixed in the fiberboard, and the fiberboard performance has been greatly improved. The attached figure shows that by adding flocculants, the modifier in the flocculant is more likely to release metal ions (Mg 2+ 、Al 3+ ) combines with silicon ions in the silica sol to form new metal bonds (Si-OM), which inhibits the hydrophilic groups -OH on the surface of SiO2 particles in the silica sol from aggregating to the surface as H2O evaporates during the drying process, and uniformly fixes SiO2 inside the fiberboard by forming new metal bonds.

[0344] The modified zero-emission wastewater green high-strength inorganic fiber insulation board has smaller and more uniform internal pores, which reduces thermal conductivity, increases porosity, and greatly improves the compressive strength of the fiberboard. Compared with the existing preparation technology, the zero-emission wastewater high-strength inorganic fiber insulation board prepared in this specific embodiment has more excellent mechanical properties and thermal insulation properties.

[0345] The zero-emission wastewater green high-strength inorganic fiber insulation board prepared in this specific embodiment is tested: the volume density is 0.28-0.69 g / cm 3 ; Surface hardness is 26~72HA; Center hardness is: 22~66HA; Compressive strength is 0.22~0.82MPa; Thermal conductivity at room temperature is 0.0677~0.0737W / (m·K).

[0346] Therefore, this specific embodiment has the characteristics of resource recovery, green cycle without wastewater discharge, simple process, low production cost and low energy consumption, and is a method for preparing a zero-emission wastewater green high-strength inorganic fiber insulation board; the manufactured products not only have excellent mechanical properties and high compressive strength, but also have low thermal conductivity, low volume density and high porosity.

Claims

1. A method for preparing a green high-strength inorganic fiber insulation board with zero wastewater discharge, characterized in that The steps of the preparation method are: Step 1, 6.0-8.0 parts by weight of calcium magnesium silicate fiber and 69.0-71.0 parts by weight of deionized water are mixed and stirred rapidly to obtain a first mixture I; or 5.0-6.0 parts by weight of aluminum silicate fiber and 70.0-72.0 parts by weight of deionized water are mixed and stirred rapidly to obtain a first mixture I'; Step 2: Under stirring conditions, 23.0-25.0 parts by weight of silica sol are added to the first mixture I and the first mixture I', respectively, to obtain the first mixture II and the first mixture II'; then 0.1-0.5 parts by weight of a modifier is mixed with 2-3 parts by weight of a 2wt% citric acid aqueous solution to obtain a flocculant; and the flocculant is added to the first mixture II and the first mixture II', respectively, and stirred to obtain the first mixture III and the first mixture III'; Step 3, preparation of zero-wastewater-discharge green high-strength inorganic fiber insulation board, the preparation method is A1 method or B1 method, the A1 method is carried out according to the following steps 3.1 to 3.2, and the B1 method is carried out according to the following steps 3.1 to 3.3; Step 3.1, filtering the first mixed material III and the first mixed material III' respectively under the condition of a vacuum degree of -0.088 to -0.098 MPa to obtain a first filtrate I and a first wet blank I, a first filtrate I' and a first wet blank I'; The first wet blank I and the first wet blank I' are dried in an air atmosphere at 100-110° C. for 10-12 hours, and cooled to obtain the first zero-wastewater discharge green high-strength inorganic fiber insulation board I and the first zero-wastewater discharge green high-strength inorganic fiber insulation board I'; Step 3.2, adding calcium magnesium silicate fiber to the first filtrate I to the mass parts described in step 1, or adding aluminum silicate fiber to the first filtrate I' to the mass parts described in step 1, stirring and vacuum filtering respectively to obtain a first filtrate II and a first wet blank II, a first filtrate II' and a first wet blank II'; The first wet blank II and the first wet blank II' are dried in an air atmosphere at 100-110° C. for 10-12 hours, and cooled to obtain the first zero-wastewater discharge green high-strength inorganic fiber insulation board II and the first zero-wastewater discharge green high-strength inorganic fiber insulation board II'; Step 3.3, adding magnesium calcium silicate fiber to the first filtrate II to the mass parts described in step 1, or adding aluminum silicate fiber to the first filtrate II' to the mass parts described in step 1, stirring and vacuum filtering respectively to obtain a first filtrate III and a first wet blank III, a first filtrate III' and a first wet blank III'; The first wet blank III and the first wet blank III' are dried in an air atmosphere at 100-110° C. for 10-12 hours, cooled, and the first zero-wastewater discharge green high-strength inorganic fiber insulation board III and the first zero-wastewater discharge green high-strength inorganic fiber insulation board III' are obtained; Step 3.4, according to method A1 or method B1, add calcium magnesium silicate fiber to the first filtrate II filtered twice or the first filtrate III filtered three times to the mass parts described in step 1, or add aluminum silicate fiber to the first filtrate II' filtered twice or the first filtrate III' filtered three times to the mass parts described in step 1, and then add silica sol, flocculant and deionized water to the mass parts described in step 2, respectively, to obtain the second mixed material I and the second mixed material I'; Step 4, according to step 3, a second preparation of zero-discharge wastewater green high-strength inorganic fiber insulation board is performed, and the preparation method is A2 method or B2 method, the A2 method is performed according to the following steps 4.1 to 4.2, and the B2 method is performed according to the following steps 4.1 to 4.3; Step 4.1, filtering the second mixed material I and the second mixed material I' respectively under the condition of a vacuum degree of -0.088 to -0.098 MPa to obtain a second filtrate I and a second wet blank I, a second filtrate I' and a second wet blank I'; The obtained second wet blank I and second wet blank I' are dried in air atmosphere at 100-110° C. for 10-12 hours, cooled, and the second zero-wastewater discharge green high-strength inorganic fiber insulation board I and the second zero-wastewater discharge green high-strength inorganic fiber insulation board I' are obtained; Step 4.2, adding magnesium calcium silicate fiber to the second filtrate I to the mass parts described in step 1, or adding aluminum silicate fiber to the second filtrate I' to the mass parts described in step 1, stirring and vacuum filtering respectively to obtain a second filtrate II and a second wet blank II, a second filtrate II' and a second wet blank II'; The obtained second wet blank II and second wet blank II' are dried in air atmosphere at 100-110° C. for 10-12 hours, cooled, and the second zero-wastewater discharge green high-strength inorganic fiber insulation board II and the second zero-wastewater discharge green high-strength inorganic fiber insulation board II' are obtained; Step 4.3, adding calcium magnesium silicate fiber to the second filtrate II to the mass parts described in step 1, or adding aluminum silicate fiber to the second filtrate II' to the mass parts described in step 1, stirring and vacuum filtering respectively to obtain a second filtrate III and a second wet blank III, a second filtrate III' and a second wet blank III'; The obtained second wet blank III and second wet blank III' are dried in air atmosphere at 100-110° C. for 10-12 hours, cooled, and the second zero-wastewater discharge green high-strength inorganic fiber insulation board III and the second zero-wastewater discharge green high-strength inorganic fiber insulation board III' are obtained; Step 4.4, according to method A2 or method B2, adding calcium magnesium silicate fiber to the second filtrate II filtered twice or the second filtrate III filtered three times to the mass parts described in step 1, or adding aluminum silicate fiber to the second filtrate II' filtered twice or the second filtrate III' filtered three times to the mass parts described in step 1, and then adding silica sol, flocculant and deionized water to the mass parts described in step 2, respectively, to obtain a third mixed material I and a third mixed material I'; Cycle in sequence; Step 2+n, according to step 3, the preparation of the nth zero-discharge wastewater green high-strength inorganic fiber insulation board is carried out, and the preparation method is An method or Bn method, the An method is carried out according to the following steps 2+n.1 to 2+n.2, and the Bn method is carried out according to the following steps 2+n.1 to 2+n.3; Step 2+n.1, filtering the nth mixed material I and the nth mixed material I' under a vacuum degree of -0.088 to -0.098 MPa to obtain the nth filtrate I and the nth wet blank I, the nth filtrate I' and the nth wet blank I'; The prepared nth wet blank I and nth wet blank I' are dried in air atmosphere at 100-110° C. for 10-12 hours, cooled, and the nth zero-discharge wastewater green high-strength inorganic fiber insulation board I and the nth zero-discharge wastewater green high-strength inorganic fiber insulation board I' are obtained; Step 2+n.2, adding magnesium calcium silicate fiber to the nth filtrate I to the mass parts described in step 1, or adding aluminum silicate fiber to the nth filtrate I' to the mass parts described in step 1, stirring and vacuum filtering respectively to obtain the nth filtrate II and the nth wet blank II, the nth filtrate II' and the nth wet blank II'; The prepared nth wet blank II and nth wet blank II' are dried in air atmosphere at 100-110° C. for 10-12 hours, cooled, and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board II and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board II' are obtained; Step 2+n.3, adding magnesium calcium silicate fiber to the nth filtrate II to the mass fraction described in step 1, or adding aluminum silicate fiber to the nth filtrate II' to the mass fraction described in step 1, stirring and vacuum filtering respectively to obtain the nth filtrate III and the nth wet blank III, the nth filtrate III' and the nth wet blank III'; The prepared nth wet blank III and nth wet blank III' are dried in air atmosphere at 100-110° C. for 10-12 hours, cooled, and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board III and the nth zero-wastewater discharge green high-strength inorganic fiber insulation board III' are obtained; n is a positive integer ≥30.

2. The method for preparing the zero-wastewater-discharge green high-strength inorganic fiber insulation board according to claim 1, characterized in that: The main chemical components of the calcium magnesium silicate fiber are: MgO≥3.7wt%, SiO2≥64.8wt%, CaO≥28.9wt%, Al2O3≤0.8wt%; the diameter of the calcium magnesium silicate fiber is ≤4μm.

3. The method for preparing the zero-wastewater-discharge green high-strength inorganic fiber insulation board according to claim 1, characterized in that: The main chemical components of the aluminum silicate fiber are: Al2O3≥44.0wt%, SiO2≥54.0wt%, Fe2O3≤0.6wt%, Na2O≤0.2wt%, K2O≤0.2wt%; the diameter of the aluminum silicate fiber is ≤4μm.

4. The method for preparing the zero-wastewater-discharge green high-strength inorganic fiber insulation board according to claim 1, characterized in that: The SiO2 content of the silica sol is 20-22 wt %, and the pH value of the silica sol is 9.5-10.

5.

5. The method for preparing the zero-wastewater-discharge green high-strength inorganic fiber insulation board according to claim 1, characterized in that: The modifier is one of attapulgite: α-Al2O3: montmorillonite: γ-Al2O3: nano-Al2O3 in a molar ratio of 4:3:1:1:1, 4:2:2:1:1, 4:1:1:2:2, 3:3:2:1:1, 2:3:3:1:1, 1:4:3:1:1, 1:3:3:2:1, and 1:3:2:3:

1.

6. The method for preparing the zero-wastewater-discharge green high-strength inorganic fiber insulation board according to claim 1, characterized in that: The α-Al2O3 is milled to a particle size of d using a planetary ball mill at a ball to material ratio of 3:

1. 50 The grinding balls of the ball mill are made of corundum, and the ball milling medium is deionized water.

7. The method for preparing the zero-wastewater-discharge green high-strength inorganic fiber insulation board according to claim 1, characterized in that: The rotation speed of the rapid stirring is 1000-1100 r / min.

8. A zero-wastewater green high-strength inorganic fiber insulation board, characterized in that The zero-wastewater discharge green high-strength inorganic fiber insulation board is a zero-wastewater discharge green high-strength inorganic fiber insulation board prepared by the preparation method of the zero-wastewater discharge green high-strength inorganic fiber insulation board according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of hollow mullite heat-insulation fiber

    CN110156447A

  • A high-strength nano-insulating material and its preparation method

    CN110790530B

  • Nano thermal insulation material and preparation method thereof

    CN113024267A

  • Preparation method of thermal insulation cellulose aerogel composite material

    CN115975251A

  • Porous insulating fiber board

    CN202483022U